(untitled) (Bioagro, 2020)
In Venezuela, orange is important as fresh fruit and for the concentrate industry. It is possible that harvesting in an inadequate period may reduce industrial efficiency due to poor quality of the fruits. This work evaluates the fruit quality evolution in order to suggest the best harvest time for oranges coming from the Durute zone, Yaracuy State. Records of the quality control laboratory of Multifruit processing plant from 2009-2010 to 2013-2014 harvests were considered. Durute´s orchards with greatest regularity and volume delivered to industry were selected, and juice yield, soluble solids (SS), titratable acidity (TA), SS/TA ratio, and concentrate yield (CY) were evaluated. The main effects of harvest day and year were considered, and correlation tests were carried out between harvest day and fruit quality variables. Orange quality was influenced individually and combined by harvest day and year. Fruit quality evolution was affected by harvest day, and there were associations with TA, SS/ TA ratio and CY yield. The fruit with best quality can be harvested any day between 100 and 200 days after harvest, which corresponds to the January to April period of the year.